Solid state interactions in the systems CaO(CaCO3)-Fe2O3 and CuFe2O4-CaO - Boyanov B.S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The solid state interactions in the systems CaO(CaCO3)-Fe2O3 and CuFe2O4-CaO have been studied using X-ray diffraction analysis. The influence of the temperature on the ferrite formation process has been investigated in the range of 900-1200 oC and duration up to 360 min. It has been shown that a mixture of ferrites forms at 1000 oC and interaction of 240 min. The exchange reactions in the systems CuFe2O4-CaO and Cu0.5Zn0.5Fe2O4-CaO have been studied, too. It has been established that Ca2+ ions exchange Cu2+ and Zn2 partially and the solubility of copper and zinc in a 7 % sulfuric acid solution increases 10-15 times.